(3BOGH GdYGde hGdeJYdes - (3Ydj Hf YHO Gddg Hf CMeO GdMSfj GdTGaYj, fhQ GdOjf CHh GdMSf,J (B911 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdgGOi Edi WQjb GdUhGH hHYO agPg cQGQjS eSJMHI ef cJGH LhGgQ GdYbOjf ai aVd GdTQjajf TQa GdYde GdLdi hGdfSH GdfHhi GdaUd GdChd ai BOGH GdYGde s
(3BNQgG (B:s
(3Yf GHf YHGS QVi Gddg YfgeG Cf fHi Gddg Udi Gddg Ydjg hEdg hSde bGd Cf GdgOi GdUGdM hGdSeJ GdUGdM hGdEbJUGO LRA ef NeSI hYTQjf LRA ef GdfHhI gPG BNQ eG JjSQ LeYg ef GdYdeG hGdeJYdejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HeOGO eNJdas
(3fSNI ecQQI ef Qbe (B" 76 (3SjGSI hGLJeGY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B307 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B129s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs